Seasonal water and salt cycling in the Great Salt Lake after opening the new causeway breach - Diana Dunn; Brian M. Crookston; Colin Phillips; Som Dutta; Bethany Neilson (Journal of Hydrology: Regional Studies)
Study region: The Great Salt Lake, the largest saltwater lake in the western hemisphere, located in Utah, USA. Study focus: A railroad causeway divides the Great Salt Lake into north and south arms and significantly alters natural lake dynamics. A new opening in the causeway, referred to as the New Breach, was completed in December 2016 to manage exchange flows between the north and south arms and control salinity primarily in the south arm. Salinity data have been collected independently by multiple stakeholders using different monitoring techniques and instrumentation. To overcome inconsistent data and provide a holistic record of salinity conditions, new methods were developed for curating and compiling all relevant disparate salinity data into a daily representative time series with quantified uncertainties for the south arm of the lake. New hydrological insights for the region: This dataset was used to characterize the altered spatial and temporal patterns of salinity within the south arm during varied hydrologic periods while considering the effects of the New Breach. Results, contextualized by data uncertainties, inform lake management by showing that the New Breach exchange flows influence lake salinity, but the primary controls are related to the balance between river inflows and evaporation. While considering dataset limitations, insights are provided regarding how monitoring at the Great Salt Lake may be improved to better support active lake management efforts.